Cell Phone Use Habits Among the Spanish Population: Contribution of Applications to Problematic Use - De-Sola, José; Rubio, Gabriel; Talledo, Hernán; Pistoni, Luis; Van Riesen, Henk; Rodríguez de Fonseca, Fernando (Frontiers in Psychiatry, 2019)
Mobile phone abuse may be associated with health problems as well as with interferences in daily life. However, beyond the mobile as a device, the contributions of specific utilities and applications to the problematic mobile phone use remains to be analyzed. To address this important question we conducted 1,126 online interviews in Spain with participants aged 16 to 65 who are representative of the general population. The aim of the study was to analyze the patterns and differences of cell phone use based on habitual use, abuse and problematic use, considering the most frequently used utilities and applications. Additional variables used were personal perception of cell phones, intensity of use, and participant`s lifestyle with regard to entertainment and the maintenance of healthy habits. Further, we aimed to analyze difference between problematic and non problematic mobile phone users in the utilization of applications, controlling for additional variables such as age, gender, educational level, consumption of tobacco and alcohol and illegal drugs. Results show that problematic use is consistent with the self-perception of abuse and is related to internet browsing, social media, music and mobile games; particular applications of interest include Facebook, music applications and Twitter. Furthermore, among problematic users, a pattern of interference with other activities or inappropriate use in certain contexts is observed, with a differential pattern of entertainment and abandonment of healthy habits. Finally, two binary logistic regression analyses demonstrated that beyond the cell phones themselves, specific utilities and applications such as browsing, chatting or downloading and listening to music contribute to the differences between problematic and non problematic users. Specifically, the use of Facebook, Twitter and music applications have the greatest power to discriminate between the two types of users.